2022
DOI: 10.1093/cercor/bhac422
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular decoupling measured with quantitative susceptibility mapping is associated with cognitive decline in patients with type 2 diabetes

Abstract: Disturbance of neurovascular coupling (NVC) is suggested to be one potential mechanism in type 2 diabetes mellitus (T2DM) associated mild cognitive impairment (MCI). However, NVC evidence derived from functional magnetic resonance imaging ignores the relationship of neuronal activity with vascular injury. Twenty-seven T2DM patients without MCI and thirty healthy controls were prospectively enrolled. Brain regions with changed susceptibility detected by quantitative susceptibility mapping (QSM) were used as see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…They suggest that NVC dysfunction is one of the potential mechanisms underlying mild cognitive impairment (MCI) associated with T2DM. Yu et al (2019) also found that certain NVC parameters could serve as biomarkers for early assessment of cognitive decline in T2DM patients, which also contribute to a better understanding of NVC mechanisms ( Ni et al, 2023 ). Additionally, three other clinical studies have identified changes in NVC during the early stages of diabetes ( Duarte et al, 2015 , 2023 ; Monteiro et al, 2021 ).…”
Section: Clinical Evidence Of Nvc Impairment In Diabetes Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that NVC dysfunction is one of the potential mechanisms underlying mild cognitive impairment (MCI) associated with T2DM. Yu et al (2019) also found that certain NVC parameters could serve as biomarkers for early assessment of cognitive decline in T2DM patients, which also contribute to a better understanding of NVC mechanisms ( Ni et al, 2023 ). Additionally, three other clinical studies have identified changes in NVC during the early stages of diabetes ( Duarte et al, 2015 , 2023 ; Monteiro et al, 2021 ).…”
Section: Clinical Evidence Of Nvc Impairment In Diabetes Patientsmentioning
confidence: 99%
“…These findings collectively validate previous conclusions that neurovascular uncoupling occurs in the early stages of T2DM and promotes the transition from diabetes-related mild cognitive impairment to dementia ( Mogi and Horiuchi, 2011 ; Duarte et al, 2015 ; Venkat et al, 2016 ; Shekhar et al, 2017 ). T2DM patients without mild cognitive impairment are considered the best target population for preventive interventions ( Yu et al, 2019 ; Kovacs-Oller et al, 2020 ; Ni et al, 2023 ). Furthermore, a longitudinal study by Zhang Y. et al (2021) over 5 years indicated that T2DM may accelerate NVC damage in specific brain regions (left insula), leading to memory decline ( Zhang Y. et al, 2021 ).…”
Section: Clinical Evidence Of Nvc Impairment In Diabetes Patientsmentioning
confidence: 99%
“…The across-voxel coupling analysis between CBF and QSM map using the multimodal image coupling analysis software was performed. 53,54 To verify the uniformity of brain anatomy and function, the AAL atlas was used to segregate the cerebrum into 116 independent regions. 52 The predefined ROIs restricted the analysis volume, with the brain images dot multiplied with the specific ROI to form the ROI-wise images.…”
Section: Analysis Of Global Cbf-susceptibility Value Couplingmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a multifaceted metabolic disorder characterized by pancreatic β-cell damage, hyperglycemia, insulin resistance, and insufficient insulin production ( 8 , 13 ). This condition is intricately associated with cognitive decline, affecting various aspects such as executive function, memory, attention, and visuospatial abilities ( 8 , 14 16 ), and manifests as structural brain alterations, such as atrophy and iron accumulation ( 16 , 17 ). The perturbation of insulin signaling exacerbates the distribution of iron in neuronal tissues, resulting in neuronal iron overload and potential complications including neuropathy ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…QSM allows for precise measurement of the magnetic susceptibility (χ) of tissues, including those of the brain ( 26 , 27 ). It has shown great promise in assessing iron concentrations within various brain structures, offering a potential window into the neurological complications associated with DM ( 17 , 28 ).…”
Section: Introductionmentioning
confidence: 99%